Use of antibiotics and about quinolones in veterinary therapy (ro) - Crina L. Mosneang; Romeo T. Cristina; Alexandru O. Doma (Medicamentul Veterinar)
In Romania are being done extensively efforts in the veterinarians education to emphasize the importance and the European regulations familiar behavior, relating to veterinary drugs prescribing, the issues of residues, of antibacterial resistance and of judicious use of the veterinary conditionigs. In this respect, the present synthesis presents an overview, a useful and necessary bibliographical remembrance to veterinary practitioner about antibiotics and quinolones in particular. Are summarized: bacterial antagonism, methods for studying the effectiveness of antibiotics, the mode of action of antibiotics, the phenomenon of resistance to antibiotics and toxic secondary phenomena caused by antibiotics, continued by information about quinolone-carbonic acid derivatives (quinolones) them action mechanism, classification and presentation of the main representatives, indications and contraindications, etc. Referate is conceived in two parts about antibiotics and about quinolones.